1972
DOI: 10.1677/joe.0.0530001
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Turnover in Rat Adenohypophyses in Vivo: Its Evaluation as a Method for Estimating Secretion Rates

Abstract: The kinetics of prolactin turnover were investigated in female rat adenohypophyses in vivo. The animals received an intravenous injection of [3H]leucine and groups were killed at various times thereafter. The prolactin in their adenohypophyses was separated and measured by disc electrophoresis and densitometry. The hormone band was cut from the gel columns and counted by liquid scintillation procedures. The specific activity data (c.p.m./\g=m\g) were fitted to single or double exponential functions by the meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1973
1973
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The doses of prolactin used are within the physiological range judging from estimates of pituitary secretion rates for prolactin. The 100 and 200 ng/min doses of prolactin, for example, are quite similar to estimates of prolactin secretion rates in cyclic (Koch et al 1971) and in oestrogen and/or reserpine-treated female rats (Swearingen & Nicoli, 1972), whereas the 472 ng/min dose is similar to estimates of prolactin secretion rates in lactating rats (Grosvenor & Whitworth, 1974). The rate of clearance of 131I-labelled prolactin did not increase with infusion rate and yielded higher values which, however, were significantly correlated with those obtained from simultaneous infusion of unlabelled prolactin.…”
Section: Non-lactating Lactatingsupporting
confidence: 62%
“…The doses of prolactin used are within the physiological range judging from estimates of pituitary secretion rates for prolactin. The 100 and 200 ng/min doses of prolactin, for example, are quite similar to estimates of prolactin secretion rates in cyclic (Koch et al 1971) and in oestrogen and/or reserpine-treated female rats (Swearingen & Nicoli, 1972), whereas the 472 ng/min dose is similar to estimates of prolactin secretion rates in lactating rats (Grosvenor & Whitworth, 1974). The rate of clearance of 131I-labelled prolactin did not increase with infusion rate and yielded higher values which, however, were significantly correlated with those obtained from simultaneous infusion of unlabelled prolactin.…”
Section: Non-lactating Lactatingsupporting
confidence: 62%
“…This effect could be the result of prolactin release by the pituitary (cf. Chen & Meites, 1970;Meites, Lu, Wuttke, Welsch, Nagasawa & Quadri, 1972;Swearingen & Nicoli, 1972). Prolactin stimulation of intestinal transport of fluid in a mammal was reported by Ramsey & Bern (1972), who also showed that adrenalectomy and nephrectomy sensitized the more distal segments of the small intestine to prolactin stimulation.…”
Section: Resultsmentioning
confidence: 92%
“…Our results are in excellent agreement with those of Jones et al (5) who eluted these proteins from the polyacrylamide gels and established their identity by bioassay. In addition, the excellent separation of rat growth hormone and prolactin by this method has been described by other workers (7)(8)(9)(10).…”
mentioning
confidence: 72%